The employment consequences of anti-dumping tariffs: Lessons from Brazil - Gustavo de Souza; Haishi Li (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
How do import tariffs affect employment? We develop an empirical strategy to identify the effects of tariffs using difference-in-differences, comparing anti-dumping (AD) investigations resulting in dumping tariffs to those not resulting in dumping tariffs. We find that an AD tariff decreases imports and increases employment in the protected sector. Moreover, downstream firms decrease employment, while upstream ones are unaffected because the protected sector sources inputs abroad. Using a model to quantify the aggregate effects, we find that the Brazilian AD policy increased employment by 0.06% at a welfare loss of 2.4%.
Keywords: F13; F16; 330; employment; tariffs; anti-dumping; international trade